2022
DOI: 10.3390/jdb11010001
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding the Genetic Mechanisms of Zebrafish Renal Multiciliated Cell Development

Abstract: Cilia are microtubule-based organelles that project from the cell surface. In humans and other vertebrates, possession of a single cilium structure enables an assortment of cellular processes ranging from mechanosensation to fluid propulsion and locomotion. Interestingly, cells can possess a single cilium or many more, where so-called multiciliated cells (MCCs) possess apical membrane complexes with several dozen or even hundreds of motile cilia that beat in a coordinated fashion. Development of MCCs is, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 140 publications
0
6
0
Order By: Relevance
“…Understanding ciliated cell types in specific tubular segments may provide insights into the relationship between cilia and kidney development [37,52]. Our study also demonstrates that ik mutants resulted in abnormal ciliary morphology in the pronephros, but interestingly, it was restricted only to proximal renal tubules and not distal tubules.…”
Section: Discussionmentioning
confidence: 54%
“…Understanding ciliated cell types in specific tubular segments may provide insights into the relationship between cilia and kidney development [37,52]. Our study also demonstrates that ik mutants resulted in abnormal ciliary morphology in the pronephros, but interestingly, it was restricted only to proximal renal tubules and not distal tubules.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies in the zebrafish pronephros have found that decreased MCC number can be associated with aberrations in ciliogenesis (e.g. decreased cilia outgrowth) ( Chambers et al, 2020b ; Marra et al, 2019a ; Wesselman et al, 2023a ).…”
Section: Resultsmentioning
confidence: 98%
“…Within the nephron, a subpopulation of aptly named multiciliated cells (MCCs) project clusters of motile cilia into the tubule lumen and govern fluid flow [ 186 ]. MCCs are detectable via WISH as early as the 10-somite stage [ 186 ].…”
Section: Ra In Developmentmentioning
confidence: 99%
“…Within the nephron, a subpopulation of aptly named multiciliated cells (MCCs) project clusters of motile cilia into the tubule lumen and govern fluid flow [ 186 ]. MCCs are detectable via WISH as early as the 10-somite stage [ 186 ]. Much like the nephron tubule populations, MCCs are dependent on RA signaling for differentiation from the renal progenitors [ 178 ].…”
Section: Ra In Developmentmentioning
confidence: 99%